A Review on Sustainability Principles of Building: Formulation of a Theoretical Framework - Mohd Isa, Nor Kalsum; Abdul Samad, Zulkiflee; Alias, Anuar (Journal of Surveying, Construction and Property, 2014)
Sustainable development has received encouraging attention since the Rio Declaration on Environment and Development was signed in 1992 Earth Summit. In Malaysia, the focus on sustainability in building, especially in devising policies has been spelled out in the government policies at national, state and local level. It can be considered that many efforts relating to sustainability in building project have been implemented in the country, however till now sustainability in Malaysian building projects are still remain without proven. It was revealed that most of the current frameworks of sustainability in the country are not equipped to handle sustainable building project. It is often encouraged environmental measure in most cases, yet the rest of measures are less promoted. To response to the issues, this study therefore aims to explore the sustainability principles of building through the review of relevant literatures. Content analysis is used to identify the principles in the sustainability literature relevant to building projects. A theoretical framework of sustainability principles of building was then formulated to be the main outcome of the study. The framework consists of a list of 29 sustainability principles of building to be taken into account throughout the project development process. The findings is very important to be a useful starting point for future study, especially for formulating a clear guide for the development of upcoming sustainable building projects to its actual meaning.